Implementation of Food Safety for Processed Goat Milk Products Based on Hygiene and Sanitation at Ainuna Farm Dairy Milk (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Goat milk products, such as pasteurized and iced varieties, are widely consumed and provide an alternative to cow's milk as an animal protein source.  Goat milk products' food safety, however, is a critical concern that requiring attention to personal hygiene and sanitation throughout processing. The purpose of this community service project was to identify and assess the food safety procedures used by one of the MSMEs that produce dairy milk at Ainuna Farm. The methods used in this community service included a survey of the Ainuna Farm Dairy Milk MSME, interviews with the business owner, and education about food safety. The results showed that a number of habits, such as not wearing gloves, masks, or head coverings, still did not adhere to hygienic and sanitation requirements. The method of open cooling raises the possibility of contamination. The goat's milk satisfied quality standards, although it was overly flavored and colored. Sources of contamination may arised from unsanitary processing environments, including flooring, ventilation, walls, windows, and doors. To guarantee the safety of the finished product, processing equipment still needed to be improved in terms of more stringent cleanliness. Outreach initiatives were therefore carried out to raise awareness of the value of food safety and cleanliness in the production area as well as information about the processing of goat milk. The goal of this community outreach was to raise owner and staff knowledge from 83.33% to 100%. This project successfully raised awareness of the value of food safety and cleanliness, also offered suggestions for enhancing the processing method to produce safer and more hygienic goat milks for consumers.